Implementation of the Backtracking Algorithm for Optimizing Work Shift Scheduling - Ainna Khansa; Sutabri, Tata (International Journal Scientific and Professional, 2025)
This research aims to implement the backtracking algorithm for optimizing shift scheduling at PLTU SSP. The study is motivated by the complexity of manual shift scheduling, which is prone to human error and struggles to accommodate various constraints such as employee availability, preferences, and operational needs. The backtracking algorithm was selected due to its ability to search systematically for optimal solutions that satisfy all constraints, based on Depth First Search (DFS). The research methodology includes requirements analysis, system design, algorithm implementation, testing, and results evaluation. The application of the backtracking algorithm produced schedules that accurately meet constraints and consider employee preferences. The results indicate that the backtracking algorithm can generate effective and efficient schedules. The implementation of the backtracking algorithm is expected to improve the quality of shift work management, positively impacting productivity, employee welfare, and the smooth operation of PLTU SSP.